111k views
1 vote
What is the solution of 5x - 3y = - 12 & 2x + 3y = - 9

User Natevw
by
4.8k points

1 Answer

6 votes

Answer:

(x, y) = (-3, -1)

Explanation:

The y-coefficients are opposites in the two equations, so it is convenient to add the equations to eliminate the y-variable.

(5x -3y) +(2x +3y) = (-12) +(-9)

7x = -21 . . . . . . . simplify

x = -3 . . . . . . . . . divide by 7

Substituting into the second equation gives ...

2(-3) +3y = -9

-2 +y = -3 . . . . . . divide by 3

y = -1 . . . . . . . . . . add 2

The solution is (x, y) = (-3, -1).

What is the solution of 5x - 3y = - 12 & 2x + 3y = - 9-example-1
User Pavel Stepanov
by
6.2k points